Effects of 14 T high magnetic field on the formation and migration behavior of CLF-1 steel corrosion products - Shu-Feng Zhang; Yi-Ming Lyu; Lei Peng; Shan-Liang Zheng (Nuclear Materials and Energy)
The CLF-1 steel, which is a main candidate material of cooling water pipes in fusion reactor blanket being developed in China, is not only corroded by water, but also operates in high magnetic fields. The effect of magnetic field on the corrosion process of CLF-1 steel should be considered. Currently, the corrosion of fusion reactor materials in high magnetic fields at scales of 10 T has not been studied due to the lack of suitable experimental conditions for high magnetic fields. To study the influence of high magnetic fields on the corrosion process of CLF-1 steel, corrosion experiment was carried out using a superconducting steady-state magnet in 1 wt% H2O2 + 0.1 wt% NaCl solution for 2 h with the 14 T high magnetic field. A contrast experiment without the magnetic field was performed. The ANSYS software was used to simulate the distribution of magnetic flux around the sample in a 14 T magnetic field. The morphology of the samples was observed and the composition of corrosion products was analyzed. The number of corrosion pits on the sample surface increases significantly at 14 T magnetic field, and the surface corrosion products around the pits appear approximately circular in shape, while the corrosion products distributing in strip shape on sample corroded without the magnetic field. The simulations show that the maximum magnetic flux density is localized in the middle of the sample, where most of the corrosion pits are distributed. Possible reasons for the influence of the magnetic field on the corrosion process could be that the Lorentz force and magnetic gradient force induced change the motion of ions and paramagnetic substances (such as O2) respectively.